Motivation, self-determination, and long-term weight control - Teixeira Pedro J; Silva Marlene N; Mata Jutta; Palmeira António L; Markland David (BMC, 2012)
Abstract This article explores the topics of motivation and self-regulation in the context of weight management and related behaviors. We focus on the role of a qualitative approach to address motivation - not only considering the level but also type of motivation - in weight control and related behaviors. We critically discuss the operationalization of motivation in current weight control programs, present a complementary approach to understanding motivation based on self-determination theory, and review empirical findings from weight control studies that have used self-determination theory measures and assessed their association with weight outcomes. Weight loss studies which used Motivational Interviewing (MI) are also reviewed, considering MI's focus on enhancing internal motivation. We hypothesize that current weight control interventions may have been less successful with weight maintenance in part due to their relative disregard of qualitative dimensions of motivation, such as level of perceived autonomy, often resulting in a motivational disconnect between weight loss and weight-related behaviors. We suggest that if individuals fully endorse weight loss-related behavioral goals and feel not just competent but also autonomous about reaching them, as suggested by self-determination theory, their efforts are more likely to result in long-lasting behavior change.